Smokeless tobacco utilization among tribal communities in India: A population-based cross-sectional analysis of the Global Adult Tobacco Survey, 2016–2017 - Ritik Agrawal; Shishirendu Ghosal; Jogesh Murmu; Abhinav Sinha; Harpreet Kaur; Srikanta Kanungo; Sanghamitra Pati (Frontiers in Public Health, 2023)
IntroductionEvidence on smokeless tobacco use is scarce among indigenous communities, with the available literature based either on a specific tribe or on a particular region. Therefore, we aimed to estimate the prevalence of smokeless tobacco and assess its correlation among tribal communities in India.MethodsWe utilized data from the Global Adult Tobacco Survey-2 conducted in 2016–2017. A total of 12,854 tribal people aged >15 years were included in this study. The utilization of smokeless tobacco was estimated using the weighted proportion, and its correlates were assessed by multivariable logistic regression reported as an adjusted odds ratio (AOR) with a 95% confidence interval.ResultsThe prevalence of smokeless tobacco use was 32%. Participants aged 31–45 years [AOR: 1.66 (1.37–2.00)], who were men [AOR: 2.37 (1.94–1.90)], and who were daily wage/casual laborers [AOR: 5.32 (3.39–8.34)] were observed to have a significant association with smokeless tobacco. Willingness and attempt to quit smokeless tobacco were higher in Eastern India (31.2%) and central India (33.6%), respectively.DiscussionWe observed one-third of the tribal individuals used smokeless tobacco in India. Tobacco control policies should prioritize men, rural residents, and individuals with fewer years of schooling. Culturally appropriate and linguistically tailored messages are required for behavioral change communication.